IMPROVING CARRYING CAPACITY BY DEVELOPING RAINWATER HARVESTING: A CASE OF OYO WATERSHED, GUNUNGKIDUL, INDONESIA - Brontowiyono, Widodo; Lupiyanto, R; Malik, A.H. (Teknik Lingkungan Universitas Islam Indonesia, 2009)
Oyo watershed, which mainly consists of rural area with 517,352 inhabitants and 0.65%/annum populationgrowth, is one of degraded watersheds in Indonesia. Although the local government has formulated variouswatershed developments, the agriculture productivity of this area is still low. Water resources are the mainfactor that influences the low carrying capacity of its agriculture sector. Its abundant water availability(225,278,277 m3/year) indicates the potential water carrying capacity. With the annual rainfall of 1,858 mmand the low water demand (25,095,223 m3/year), it has a potential water surplus of 200,183,054 m3/year. Inreality, due to the low rainwater harvesting, the carrying capacity is also low, indicated by the value of 0.67with the population pressure of 1.49. This causes a revenue deficit for farmers who earn Rp 160,017.36million/year while the normal living cost is Rp 2,483,289.60 million. This indicates the low optimality of waterresources management. Therefore, the main target of Oyo Watershed management program is to use theavailable rainwater optimally to guarantee the stability of water availability in dry seasons.